2011
DOI: 10.3109/03009734.2011.628422
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal variations of insulin sensitivity from a euglycemic insulin clamp in elderly men

Abstract: Introduction.Seasonal variations in hemoglobin-A1c have been reported in diabetic patients, but the underlying mechanisms have not been elucidated.Aims.To study if insulin sensitivity, insulin secretion, and fasting plasma glucose showed seasonal variations in a Swedish population-based cohort of elderly men.Methods.Altogether 1117 men were investigated with a euglycemic insulin clamp and measurements of fasting plasma glucose and insulin secretion after an oral glucose tolerance test. Values were analyzed in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
31
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 23 publications
3
31
4
Order By: Relevance
“…Evidence from epidemiological research suggests seasonal differences in HbA1c and clinical onset of diabetes, with warmer temperatures (summer) favouring lower HbA1c and lower incidence of diabetes compared to cooler temperatures (winter). Conversely, there is a paucity of recent, well‐controlled experimental studies employing technological advancements, such as an environmental chamber, using the gold standard glucose clamp technique, to investigate the effects of ambient temperature on insulin action; such studies could provide evidence of a cause‐effect relationship. Nevertheless, there is increasing evidence of the local effects of temperature on insulin pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…Evidence from epidemiological research suggests seasonal differences in HbA1c and clinical onset of diabetes, with warmer temperatures (summer) favouring lower HbA1c and lower incidence of diabetes compared to cooler temperatures (winter). Conversely, there is a paucity of recent, well‐controlled experimental studies employing technological advancements, such as an environmental chamber, using the gold standard glucose clamp technique, to investigate the effects of ambient temperature on insulin action; such studies could provide evidence of a cause‐effect relationship. Nevertheless, there is increasing evidence of the local effects of temperature on insulin pharmacodynamics and pharmacokinetics.…”
Section: Introductionmentioning
confidence: 99%
“…5 More recently, a Swedish analysis found a contradictory result, as insulin sensitivity was lower in winter than in summer. 6 Furthermore, the same study showed no significant association between fasting plasma glucose and seasonality. Interestingly, in line with the findings of Berglund and colleagues, 6 it has been suggested that 25-hydroxyvitamin D may decrease insulin resistance and may protect against the risk of developing T2DM.…”
Section: Original Articlementioning
confidence: 92%
“…6 Furthermore, the same study showed no significant association between fasting plasma glucose and seasonality. Interestingly, in line with the findings of Berglund and colleagues, 6 it has been suggested that 25-hydroxyvitamin D may decrease insulin resistance and may protect against the risk of developing T2DM. 7 However, even though these results are of great interest, little is known about the impact of seasons on the insulin needs of patients affected by diabetes.…”
Section: Original Articlementioning
confidence: 92%
See 2 more Smart Citations